2016
DOI: 10.1080/19491034.2016.1212797
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors dynamically control the spatial organization of the yeast genome

Abstract: In yeast, inducible genes such as INO1, PRM1 and HIS4 reposition from the nucleoplasm to nuclear periphery upon activation. This leads to a physical interaction with nuclear pore complex (NPC), interchromosomal clustering, and stronger transcription. Repositioning to the nuclear periphery is controlled by cis-acting transcription factor (TF) binding sites located within the promoters of these genes and the TFs that bind to them. Such elements are both necessary and sufficient to control positioning of genes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In yeast, which does not have a NL, there is extensive evidence that NPCs can interact with specific genes as well as telomeres (Ibarra and Hetzer, 2015; Randise-Hinchliff and Brickner, 2016). In metazoans, the picture is more complex.…”
Section: Lads Do Not Appear To Be Linked To Nuclear Pore Complexesmentioning
confidence: 99%
“…In yeast, which does not have a NL, there is extensive evidence that NPCs can interact with specific genes as well as telomeres (Ibarra and Hetzer, 2015; Randise-Hinchliff and Brickner, 2016). In metazoans, the picture is more complex.…”
Section: Lads Do Not Appear To Be Linked To Nuclear Pore Complexesmentioning
confidence: 99%
“…Targeting to the nuclear periphery for several yeast genes has been shown to rely on cis-DNA sequences in their promoters known as Gene Recruitment Sequences (GRSs) (recently reviewed in [27]) (Figure 1). Interestingly, several GRSs have been shown to represent binding sites for transcription factors which ultimately mediate gene-relocation [21].…”
Section: Gene Expression Regulation By Npcs In Yeastmentioning
confidence: 99%
“…Interestingly, several GRSs have been shown to represent binding sites for transcription factors which ultimately mediate gene-relocation [21]. For INO1 it was identified that NPC-tethering is mediated by the transcription factors Put3 [28] and Cbf1 [27], which do not directly regulate the activity of this gene. Conversely, the Ste12 and Gcn4 transcription factors required for repositioning of PRM1 and HIS4 also regulate the activity of these genes [21].…”
Section: Gene Expression Regulation By Npcs In Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…Hierarchical and spatial distribution of chromosomes, chromatin domains and coregulated gene loci is tightly regulated through association with specific nuclear structures and protein complexes. Studies in yeast, fruit flies, humans and plants indicate that the position of a gene within the nucleus can influence its transcriptional potency (Gibcus & Dekker, 2013;Liu & Weigel, 2015;Randise-Hinchliff & Brickner, 2016). Major developmental reprogramming events are usually accompanied by repositioning of gene loci towards the nuclear interior, the periphery or proximally to chromocentres depending on the species and the associated proteins that will determine the extent of gene activation or silencing (Takizawa et al, 2008;Feng et al, 2014;Bourbousse et al, 2015;Wang et al, 2015;Randise-Hinchliff & Brickner, 2016;Rodriguez-Granados et al, 2016).…”
Section: Light Shapes Nuclear Architecturementioning
confidence: 99%